#### Answer

$\frac{Rs}{s-R}=g$

#### Work Step by Step

$R=\frac{gs}{g+s}$
Our problem is asking us to find out what does g equal. Our first step is to multiply both sides by (g+s). This has to be done in order to get rid of the fraction.
$R\times(g+s)=\frac{gs}{g+s}\times(g+s)$
The fraction is now canceled out because it is being multiplied by its denominator. We will now distribute the variable $R$.
$Rg+Rs=gs$
Now we subtract Rg from both sides.
$Rg-(Rg)+Rs=gs-(Rg)$
$Rs=gs-Rg$
We now factor out g.
$Rs=g(s-R)$
Here we divide both sides by (s-R).
$\frac{Rs}{s-R}=g\frac{s-R}{s-R}$
The fraction will cancel itself out. Our answer should now be
$\frac{Rs}{s-R}=g$